Sensitivity analysis and comparative studies for energy sustainability in sewage treatment. (February 2017) - Halaby, A.; Ghoneim, W.; Helal, A.
Highlights: Solar, wind and ADG variations have low, average and high impact on NPC respectively. CHP proves highly effective against PV and WTS even if its capital cost is much higher. The presented system NPC is very competitive with grid-extension case. The presented system NPC is superior versus diesel generator with real fuel prices. The presented hybrid system reduces emissions by 83% compared to grid supply. Abstract: The paper presents the sensitivity analysis for the utilization of renewable energy sources in wastewater treatment field and the related comparative studies versus conventional power sources. A former work introduced a case-study wastewater treatment plant. It discussed the feasibility of using entirely renewable hybrid system to power the plant under off-grid conditions with minimum life cycle cost and minimum possible emissions. The hybrid power system optimum configuration consisted of fuel cell, micro-turbine, wind turbine and photovoltaic systems. The sensitivity analysis in this paper aims at identifying the system effective variables in the case-study. This is to derive general rule-of-thumbs which express the system behavior. Through using HOMER software, the sensitivity analysis studies the effect of renewable energy potentials and the capital cost of the power subsystems. Besides, the paper measures the feasibility strength of the base hybrid system by holding Comparisons with conventional power systems. The comparative studies determine the breakpoints and feasibility zones which grant the preference of the hybrid system.